Liberdade, igualdade e amor: perspectivas para uma ética em Nicolau de Cusa (1401-1464) - Souza, Klédson Tiago Alves de (2018)
The problematic question that will underline this dissertation will be the following: the possible existence in the works of Nicholas of Cusa in some aspect that offers us a reflection on ethics, even though he did not specifically write anything on this theme. As a hypothesis we see the possibility of discovering ethics in his texts, while considering that these texts are geared to debate the human mind´s tendency to Truth. However, we conclude that in this reflexsive state there is a possibility of contemplating ethics. The core of our discussion is based on the relation and position that Nicholas of Cusa assumes in relation to Truth , since for him the essence of the human being is completely in its relation to Truth. Man has an ardent desire for happiness and that longing can only be attained in knowing the Truth that he seeks. It is a known fact that there is not a systematic work on ethics that the Cardinal could have written. Besides this, the ethical aspect present in his works continues in a configuration of human behavior in the pursuit of his existence as a task. To reach our goal we divided our presentation into three chapters: the exploitation of the metaphysical concepts complication, explication e contractio and their articulations; the inerrant dynamism in the search of the absolute truth, this dynamism being the result of the contraction. In the second chapter, three steps will be important to consider: the characterization of man as singular, and to think of man as viva imago dei and his place as mediator. If man is natura media it is important to take a further step wherein he can be seen as a symbol of symbols. In this sense, man realizes a finality of understanding the glory and the praise to God through the interpretation of things. The third chapter is divided in three moments: the first is the cognitio sui, that makes man realize the traces of the trinity in him and his triplicate participation (sensus, ratio et intellectus) in the absolute one-trinity (unitas, aequalitas et conexio) the first step in the being created in God´s image and after this self-knowledge it will be important to think and work at the idea of one´s full possession of self, using the formula sis tuus et ego ero tuus.The second moment is to think out freedom. This theme is essential and will be considered in articulating aa motive s f the microcosmos and of the capax dei. The life that God gives man possesses the gift of free will where he can restrict or augment his participation from the start. In the third and final moment we will demonstrate two important aspects and its complements to the ethical-gnostic logic of Nicholas of Cusa: justice as a contracted means of the aequalitas and caritas as a form of of a practiced faith. Lastly, we will address this segment of imperative ethics or the law of equality. With that configuration of the census we trust in making explicit ethics in Nicholas of Cusa´s works or at least shedding a bit more light on this question.